Orthotic Care Based on the Ferrari Concept for Children and Adults with Meningomyelocele - Schmid, Tim; Strehl, Elisabeth; Trollmann, Regina; Forst, Raimund; Fujak, Albert (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Even today, myelomeningocele (MMC) is still encountered in clinical medicine and its incidence has not decreased over the last 20 years despite a known reduction in risk due to the use of folic acid supplements. The spectrum of clinical symptoms is extremely broad and, depending on the level of the defect, varies from mild to severe. Subject to the degree of paralysis, patients are reliant on the use of orthopaedic aids and orthoses for the treatment of primary contractures and deformities and the prevention of secondary ones. This forms the basis for attaining or maintaining mobility in many patients. The objective of the study was to determine the practical application of the proposed Ferrari concept for the provision of orthoses for children and adults. Patients and Material The retrospective study comprised medical records of 180 patients (97 m) with an average age of 19.44 years (3-52 years, SD 9.3) at the time of investigation. The average duration of treatment was 15.34 years (1-38 years, SD 8.96). Data relating to deformities of the vertebral column and lower limbs, provision of hydrocephalus shunts and orthoses, and patient mobility was evaluated. Results Most patients were given systematic treatment with orthoses at an early stage. In 58,9% of cases, it was possible to implement the proposed concept for providing patients with dynamic orthoses, whereby the treatment concept was more difficult to implement with high lumbar lesions than with lower lesions. Moreover, a decrease in the patients' mobility with increasing age was noticeable. Some 42.3% of adult patients were able to walk with marked variations in mobility in relation to the different levels of lesions. Conclusion Taking into consideration the complexity of both the clinical picture and therefore the provision of orthopaedic devices, the result of the implementation of the proposed orthotic concept can be considered positive. Similarly, early commencement of provision of orthoses and hence the possibility of achieving a positive influence on later mobility can be considered a success. The need for individual concepts and further development in order to increase mobility particularly in the case of patients with thoracic or high lumbar lesions is evident. A more comprehensive provision of information to patients regarding orthotic treatment options and their consequences for prophylaxis and quality of life should be an important component of interdisciplinary long-term patient care.
CRIS-Team Scopus Importer:2019-12-13
Keywords: MMC; mobility; orthopaedic treatment concept; orthotics